Strategi Perbankan Indonesia Terhadap Eksistensi Bank Dalam Pasar Valuta Asing Guna Mendukung Penguatan Rupiah di Tengah Fluktuasi Ekonomi Global - Hermawan, Mohammad Fariz Nur Agung; Hafidz, Rafli Muhammad; Rifa’i, Rizky Nanda; Suwarsit, Suwarsit (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
One of the most important components in national and international economic stability is the foreign exchange market, or forex. As a major player in the financial sector, banks have a very important strategic role in maintaining exchange rate stability and controlling foreign exchange flows. Law No. 7/2011 on Currency, Law No. 23/1999 on Bank Indonesia, as last amended by Law No. 6/2009, and Bank Indonesia (BI) regulations are some of the laws relating to the foreign exchange market in Indonesia. Changes around the world have also made it more important for BI and OJK to work more closely together, BI must ensure that BI's macroprudential policies complement OJK's microprudential supervisory procedures as the institution responsible for monetary stability. As the country's central bank, BI's primary responsibility is to maintain the stability of the Rupiah exchange rate. BI often intervenes in the foreign exchange market to control the movement of the Rupiah exchange rate in order to carry out its functions. BI is also responsible for supervising and controlling banking activities in Indonesia to prevent financial disasters. Dealing with international factors that affect currency exchange rates and domestic economic stability is crucial. In general, the tightening of supervision of banks involved in foreign exchange transactions aims to promote sustainable national economic growth by encouraging a more transparent and responsible market in addition to maintaining exchange rate stability.